Comparison for decentralized control multivariable process - Kyaw, Kyaw Htike. (2008)
In this dissertation, the design procedures of four typical decentralized PI/PID controller design methods: the biggest log modulus tuning (BLT) method, the gain and phase margin (GPM) method, the internal model control (IMC) method and the effective relative gain array (ERGA) method, are revisited first, and then implemented to ten different distillation systems that vary from two-input two-output systems up to four-input four-output systems.